Deciphering the Indus Valley/Harappan Script: A Comparative Linguistic Approach - Rishabh Bhargava (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
Symbols were taken from intact seals of the Indus Valley/Harappan civilisation and analysed for similarity to other known languages. Identical symbols were demonstrated. Text from 8 Indus Script seals were analysed and appeared to be related to the Germanic languages. The symbols identical to the Germanic languages were present in multiple seals from the Indus Valley/Harappan period and, therefore, may help elucidate some of the meaning of the Indus Script.